Energy Distribution of Secondary Particles in Ion Beam Deposition Process of Ag: Experiment, Calculation and Simulation. Issue 10 (December 2015) - Bundesmann, C.; Feder, R.; Lautenschläger, T.; Neumann, H.
Abstract: Ion beam sputter deposition allows tailoring the properties of the film‐forming, secondary particles (sputtered target particles and backscattered primary particles) and, hence, thin film properties by changing ion beam (ion energy, ion species) and geometrical parameters (ion incidence angle, polar emission angle). In particular, the energy distribution of secondary particles and their influence on the ion beam deposition process of Ag was studied in dependence on process parameters. Energy‐selective mass spectrometry was used to measure the energy distribution of sputtered and backscattered ions. The energy distribution of the sputtered particles shows, in accordance with theory, a maximum at low energy and an E –2 decay for energies above the maximum. If the sum of incidence angle and polar emission angle is larger than 90°, additional contributions due to direct sputtering events occur. The energy distribution of the backscattered primary particles can show contributions by scattering at target particles and at implanted primary particles. The occurrence of these contributions depends again strongly on the scattering geometry but also on the primary ion species. The energy of directly sputtered and backscattered particles was calculated using equations based on simple two‐particle‐interaction whereas the energy distribution was simulated using the well‐known Monte Carlo code TRIM.SP. In principal, the calculation and simulation data agree well with the experimental findings. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)